Skrivnost kabineta 209 b - Hladnik, Miran (Jezik in slovstvo, 2021)
The article presents a database of 12,000 poems of Slovenian national liberation poetry from 1941 to 1945, created under the direction of Boris Paternu at the Faculty of Arts of the University of Ljubljana in the 1970s, especially its overlooked and unused digital version, as evidenced by a computer printout of the catalogue from 1980 and 1981. This was one of the first contacts of Slovenian literature with computers. The webification of the collection has begun with the redigitisation of the catalogue. This will protect the sensitive unique material from destruction and greatly increase its usefulness, e.g., for stylometric analyses and for the identification of unauthorised verses on more than a thousand Slovenian partisan monuments.
Keywords: 1941-1942; 1941-1945; database; digitalizacija; digitisation; National Liberation War; NOB; podatkovna zbirka; Slovenian literature; Slovenian poetry; Slovenian Second World War resistance poetry; slovenska književnost; slovenska poezija; slovensko odporniško pesništvo